Degrees of Dignity : Arab Higher Education in the Global Era. - Buckner, Elizabeth. (University of Toronto Press, 2021)
Degrees of Dignity examines how global discourses and policy models are affecting and altering contemporary higher education systems in the Arab Middle East and North Africa.